Secretion of cytokines by villous cytotrophoblast and extravillous trophoblast in the first trimester of human pregnancy - Naruse, Katsuhiko; Innes, Barbara A.; Bulmer, Judith N.; Robson, Stephen C.; Searle, Roger F.; Lash, Gendie E. (Journal of reproductive immunology, 2010)
Cytokines are proposed to play roles in regulation of trophoblast invasion, spiral artery remodeling and immunoregulation during early pregnancy. Secretion of 12 cytokines (interleukin (IL)-1β, IL-2, IL-4, IL-5, IL-8, IL-10, IL-12p70, IL-13, IFNγ, GM-CSF, MCP-1 and RANTES) by first trimester extravillous trophoblast and villous cytotrophoblast cells was examined using multiplex cytokine array technology. Seven (IL-1β, IL-8, IL-12p70, IL-13, GM-CSF, MCP-1 and RANTES) of the 12 cytokines examined were detectable in the samples studied ( n = 10 each group). Villous cytotrophoblast production of IL-1β and IL-8 increased with gestational age. Extravillous trophoblast production of IL-8, IL-13 and RANTES increased with gestational age. At 12–14 weeks gestation extravillous trophoblast cells secreted higher levels of IL-8, IL-13 and RANTES than villous cytotrophoblast cells.